Predictors of Survival in Patients with Metastatic Brain Tumors: Experience from a Low-to-Middle-Income Country - Anis, Saad Bin; Hani, Ummey; Yousaf, Irfan (Asian Journal of Neurosurgery, 2023)
Objective The interplay of static factors and their effect on metastatic brain tumor survival, especially in low-to-middle-income countries (LMICs), has been rarely studied. To audit our experience, and explore novel survival predictors, we performed a retrospective analysis of brain metastases (BM) patients at Shaukat Khanum Memorial Cancer Hospital (SKMCH), Pakistan.Materials and Methods A retrospective review was conducted of consecutive patients who presented with BM between September 2014 and September 2019 at SKMCH. Patients with incomplete records were excluded.Statistical Analysis SPSS (v.25 IBM, Armonk, New York, United States) was used to collect and analyze data via Cox-Regression and Kaplan–Meier curves.Results One-hundred patients (mean age 45.89 years) with confirmed BM were studied. Breast cancer was the commonest primary tumor. Median overall survival (OS) was 6.7 months, while the median progression-free survival (PFS) was 6 months. Age (p = 0.001), gender (p = 0.002), Eastern Cooperative Oncology Group (p < 0.05), anatomical site (p = 0.002), herniation (p < 0.05), midline shift (p = 0.002), treatment strategies (p < 0.05), and postoperative complications (p < 0.05) significantly impacted OS, with significantly poor prognosis seen with extremes of age, male gender (hazard ratio [HR]: 2.0; 95% confidence interval [CI]: 1.3–3.1; p = 0.003), leptomeningeal lesions (HR: 5.7; 95% CI: 1.1–29.7; p = 0.037), and patients presenting with uncal herniation (HR: 3.5; 95% CI: 1.9–6.3; p < 0.05). Frontal lobe lesions had a significantly better OS (HR: 0.5; 95% CI: 0.2–1.0; p = 0.049) and PFS (HR: 0.08; 95% CI: 0.02–0.42; p = 0.003).Conclusion BM has grim prognoses, with comparable survival indices between developed countries and LMICs. Early identification of both primary malignancy and metastatic lesions, followed by judicious management, is likely to significantly improve survival.
Keywords: metastatic brain tumors; brain metastasis; management strategies; overall survival; progression-free survival